Reflective Practice: A Tool for Readmission Reduction - Kashiwagi, Deanne T; Burton, M Caroline; Hakim, Fayaz A; Manning, Dennis M; Klocke, David L; Caine, Natalie A; Hembre, Kristin M; Varkey, Prathibha (American journal of medical quality, 2016)
Factors intrinsic to local practice, but not captured by the medical record, contribute to readmissions. Frontline providers familiar with their practice systems can identify these. The objective was to decrease 30-day hospital readmissions. The intervention involved retrospective review by hospitalists of their own patients' readmissions, using reflective practice guided by a chart review tool. Subjects were patients discharged by hospitalists and readmitted to a tertiary care academic medical center. Hospitalists reviewed 193 readmissions of 170 patients. Factors contributing to readmission were grouped under patient characteristics, operational factors, and care transition. After reflection, physicians scheduled earlier follow-up appointments while nurse practitioners and physician assistants improved discharge instructions. Readmissions decreased during the review period, and the decrease sustained for one year after the review period. Hospitalists reflected on and identified local practice factors that contributed to their own patients' 30-day readmissions. Reflective practice may be an effective strategy to decrease hospital readmissions.